PENGARUH KEADILAN ORGANISASI TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL DI HOTEL RAMA PHALA UBUD - Mahadi Putra, I Gede Edi Sastrawan; Indrawati, Ayu Desi (E-Jurnal Manajemen, 2018)
ABSTRACT   Organizational commitment is the desire of organization members to stay in the organization and become an important factor that contributes towards the goals of the organization. The aim of this researchmis to determine the influence of organizational justice on work satisfaction and organizational commitment in Rama Phala Hotel Ubud. This research is conducted on Rama Phala Hotel Ubud. The population in this research is all of the employees in Rama Phala Hotel Ubud. The total population sampling method is used, which results in a total of 51 sample. The data collection method is conducted by interviews and distributing questionnaires. The analysis technique utilized is the path analysis. In this research, the sobel test is used to detect the mediating variable, which is work satisfaction. The research result shows that organizational justice has positive and significant influence on work satisfaction. Work satisfaction has positive and significant influence on organizational commitment. Furthermore, work satisfaction is accepted as an intervening variable in mediating the influence of organizational justice on organizational commitment.   Keywords: organizational justice, work satisfaction, organizational commitment